1337. Medically Attended (MA) Illness Due to Respiratory Syncytial Virus (RSV) Infection among Infants in the United States during the 2016–17, 2017–18, 2018–19, and 2019–20 RSV Seasons: The Need for All-Infant Protection. (4th December 2021) - Gantenberg, Jason; Zimmerman, Nicole; Zullo, Andrew R; Limone, Brendan; Demont, Clarisse; Chaves, Sandra S; La Via, William V; Nelson, Christopher; Rizzo, Christopher; Savitz, David A; Van Aalst, Robertus
Abstract: Background: RSV-associated lower respiratory tract infection (LRTI) is the leading cause of infant hospitalization. Most studies of RSV have focused on infants with underlying comorbidities, including prematurity. The purpose of this analysis is to describe the burden of RSV LRTI across all medical settings and in all infants experiencing their first RSV season. Methods: Using de-identified claims data from two commercial (MarketScan Commercial, MSC; Optum Clinformatics, OC) and one public (MarketScan Medicaid, MSM) insurance database, we estimated the prevalence of MA RSV LRTI among infants born between April 1, 2016 and June 30, 2019 in their first RSV season. Estimates were made by gestational age, presence/absence of comorbidities, and setting (inpatient, emergency department and outpatient). Due to limited laboratory testing, we defined MA RSV LRTI using two sets of ICD-10-CM diagnosis codes: a specific definition (identifying RSV explicitly) and a sensitive definition that included unspecified bronchiolitis. The first specific diagnosis triggered a search for another MA RSV LRTI diagnosis (either specific or sensitive) within the next 7 days. In the sensitive analysis, the first diagnosis was allowed to meet the sensitive definition. Setting was recorded as the highest level of care attached to a MA RSV LRTI diagnosis within this 7-day period. Results: Using the specific (sensitive) definitions, 4.2% (12.2%), 6.8% (16.8%), and 2.7% (7.2%) of newborns had an MA RSV LRTI diagnosis during their first respiratory season across the MSC, MSM, and OC datasets (Table 1). Term infants without comorbidities accounted for 77% (83%), 79% (86%), and 80 (81%) of all MA RSV LRTI, and 21% (10%), 19% (10%), and 21% (10%) of all infants with MA RSV LRTI had an inpatient hospital stay (Table 2). Term infants without comorbidities accounted for 69% (68%), 67% (79%), and 73% (73%) of all MA RSV LRTI inpatients (Table 2). Conclusion: In commercial and public claims data, during their first RSV season, term infants without comorbidities accounted for a sizable majority of inpatient, emergency room, and outpatient encounters for RSV LRTI in the US. To address the burden of RSV LRTI, future RSV prevention efforts should target all infants. Funding: Sanofi Pasteur, AstraZeneca Disclosures: Jason Gantenberg, MPH, Sanofi Pasteur (Grant/Research Support, Scientific Research Study Investigator, Research Grant or Support) Nicole Zimmerman, MS, IBM Watson Health (Employee, Nicole Zimmerman is an employee of IBM, which was compensated by Sanofi to complete this work.)Sanofi (Other Financial or Material Support, Nicole Zimmerman is an employee of IBM, which was compensated by Sanofi to complete this work.) Andrew R. Zullo, PharmD, PhD, ScM, Sanofi Pasteur (Grant/Research Support, Research Grant or Support) Brendan Limone, PharmD, PharmD, Sanofi Pasteur (Other Financial or Material Support, IBM was contracted by Sanofi to perform analysis) Clarisse Demont, n/a, Sanofi Pasteur (Employee, Shareholder) Sandra S. Chaves, MD, MSc, Sanofi Pasteur (Employee) William V. La Via, MD, AstraZeneca (Shareholder)Sanofi Pasteur (Employee) Christopher Nelson, PhD, Epidemiology, Sanofi Pasteur (Employee) Christopher Rizzo, MD, Sanofi (Employee) David A. Savitz, PhD, Sanofi Pasteur (Grant/Research Support) Robertus Van Aalst, MSc, Sanofi Pasteur (Employee, Shareholder)